2023
DOI: 10.1371/journal.pone.0283251
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial distribution of elements, environmental effects, and economic potential of waste from the Aksu ferroalloy plant [Kazakhstan]

Abstract: The utilization or secondary use of technogenic waste is a relevant problem for the current economy. To assess the environmental influence and economic potential, it is necessary to study the elemental content of technogenic objects and to reveal the tendencies of the spatial distribution of elements, components, and indices such as the pollution coefficient. In this study, we performed elemental analysis, and calculation of indicators: average gross content, hazard quotients, concentration coefficients of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Namely, in the literature [ 141 , 142 , 143 , 144 , 145 ], it has been shown that the number of such stages can be different for different systems. Moreover, in other studies [ 143 , 144 , 145 , 162 , 163 ], it was shown that the staged nature of phase transitions can also be associated with fundamentally different processes. For example, for systems such as those studied in one study [ 144 ], it is determined by the formation of hydrophobic-hydrophilic associates (HHA), and for those studied in [ 145 ], it is determined by the formation of hydrophilic interpolymer associates (HIA).…”
Section: Methodsmentioning
confidence: 99%
“…Namely, in the literature [ 141 , 142 , 143 , 144 , 145 ], it has been shown that the number of such stages can be different for different systems. Moreover, in other studies [ 143 , 144 , 145 , 162 , 163 ], it was shown that the staged nature of phase transitions can also be associated with fundamentally different processes. For example, for systems such as those studied in one study [ 144 ], it is determined by the formation of hydrophobic-hydrophilic associates (HHA), and for those studied in [ 145 ], it is determined by the formation of hydrophilic interpolymer associates (HIA).…”
Section: Methodsmentioning
confidence: 99%